المراصد الاعلامية كآلية للتعديل الذاتي دراسة تأصيلية - بركاتي, عبد النور (جامعة الوادي - University of Eloued, 2022)
تجلت في الآونة الأخيرة مظاهرة عديدة للمراصد الإعلامية في العالم ، وأضحت احد اللاعبين المهمين في الوسط الإعلامي،حتى صارت ذات قيمة وحضور وحضوة في الأنظمة الديمقراطية التي تحترم نفسها،وصارت تصنف على أنها إحدى آليات وأدوات الرقابة ومراقبة الصالح العام، ويعول عليها في عمليات متعددة تتعلق بالرقابة والتحري والحد من سطوة الأنظمة ، والأكثر من هذا تعديل المسار المهني أو ما يعرف بالتعديل الذاتي لوسائل الإعلام من انحرافات وانزلاقات أخلاقية، وهو ما يؤكد قيمة هذه المراصد كآلية رقابية مجتمعية وأداة للتعديل الذاتي ، في شقها الغالب حول مسألة الأخلاقيات، وعمليات التنظيم والتعديل الذاتي لوسائل الإعلام In recent times, many media observatories have demonstrated in the world, and they have become one of the important players in the media community, until they have become of value, presence and presence in self-respecting democracies. Through monitoring, investigation and limiting the influence of systems, and more than this, modifying the professional path or what is known as self-modification of the media from moral deviations and slips, which confirms the value of these observatories as a societal monitoring mechanism and a tool for self-adjustment, mostly on the issue of ethics, and the processes of regulation and self-adjustment of the means media
Media observatories as a mechanism for self-adjustment Interpretive study
مقال
Keywords: المراصد، الاعلامية، التعديل الذاتي; observatories, media , Self Adjustment